2018
DOI: 10.1186/s13023-018-0835-1
|View full text |Cite
|
Sign up to set email alerts
|

How to address the challenges of evaluating treatment benefits-risks in rare diseases? A convergent mixed methods approach applied within a Merkel cell carcinoma phase 2 clinical trial

Abstract: BackgroundDemonstrating treatment benefits within clinical trials in the context of rare diseases is often methodologically and practically challenging. Mixed methods research offers an approach to overcome these challenges by combining quantitative and qualitative data, thus providing a better understanding of the research question. A convergent mixed methods design in the context of Merkel cell carcinoma, a rare skin cancer, was used during the JAVELIN Merkel 200 trial (NCT02155647).MethodsNine patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…This study in patient with treatment-naïve mMCC should be considered as complementary to the previously published study among chemotherapy refractory patients with mMCC [17][18][19].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This study in patient with treatment-naïve mMCC should be considered as complementary to the previously published study among chemotherapy refractory patients with mMCC [17][18][19].…”
Section: Discussionmentioning
confidence: 70%
“…The present article reports the findings from the qualitative interviews conducted with a large international sample of treatment-naïve patients with mMCC receiving avelumab as first-line treatment and aims to complement previous findings in patients with mMCC receiving avelumab as secondor later-line treatment [17][18][19].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The absence of improvement in the Haemo-QoL-A between the two assessments could have been the result of high scores at baseline, limiting the ability to capture significant improvement. This study emphasizes the added value of physician and patient interviews in clinical trials, in particular in rare diseases, to complement patient-reported outcome or clinical quantitative data and to gain additional insight into trial data, support interpretation of other quantitative assessments and endpoints to discuss meaningfulness of change [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%